2013
DOI: 10.1002/pi.4550
|View full text |Cite
|
Sign up to set email alerts
|

Effect of imidazolium ionic liquid type on the properties of nitrile rubber composites

Abstract: We investigated the influence of hydrophilic and hydrophobic imidazolium ionic liquids on the curing kinetic, mechanical, morphological and ionic conductivity properties of nitrile rubber composites. Two room temperature ionic liquids with a common cation—1‐ethyl‐3‐methylimidazolium thiocyanate (EMIM SCN; hydrophilic) and 1‐ethyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIM TFSI; hydrophobic)—were used. Magnesium–aluminium layered double hydroxide (MgAl‐LDH; also known as hydrotalcite) was added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 43 publications
(74 reference statements)
2
30
0
Order By: Relevance
“…23,24 Curatives must dissolve in the rubber and diffuse to the active sites to react effectively for the efficient crosslinking of rubber. 25 It can be concluded that ionic liquid improved the dispersion of curing agents particularly zinc oxide in the polymer matrix, so their presence in rubber composites contributed to a considerable decrease of vulcanization time and an increase in the crosslinking efficiency.…”
Section: View Article Onlinementioning
confidence: 99%
“…23,24 Curatives must dissolve in the rubber and diffuse to the active sites to react effectively for the efficient crosslinking of rubber. 25 It can be concluded that ionic liquid improved the dispersion of curing agents particularly zinc oxide in the polymer matrix, so their presence in rubber composites contributed to a considerable decrease of vulcanization time and an increase in the crosslinking efficiency.…”
Section: View Article Onlinementioning
confidence: 99%
“…[12] In other investigations, the electrical conductivity of IL-CNTs/CR composites increased upon accelerated thermal aging, and therefore, the authors concluded that these composites may be useful for applications where conductivity at elevated temperatures is required. [13] The use of ILs as dispersion agents has been reported not only for CNTs in a polar polychloroprene elastomer, but also in other combinations, including: ILCNTs-OH/hydrogenated nitrile rubber (HNBR), [14] IL-carbon black/solution-styrene-butadiene rubber (SSBR), [15] ILCNTs/SSBR, [16] IL-CNTs/SSBR/butadiene rubber (BR), [17] silica/styrene-butadiene rubber (SBR), [18] silica/SBR, [19] halloysite nanotubes (HNTs)/SBR, [20] IL-HNTs/ SBR, [21] silica/nitrile rubber NBR, [22] and layered double hydroxide (LDH)/carboxylated nitrile rubber (XNBR). [22] For applications in electrochemical devices, where flexibility, thermal stability and high ionic conductivity are required, polymer electrolytes are frequently based on NBR mixed with an ionic liquid and show greatly enhanced ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[13] The use of ILs as dispersion agents has been reported not only for CNTs in a polar polychloroprene elastomer, but also in other combinations, including: ILCNTs-OH/hydrogenated nitrile rubber (HNBR), [14] IL-carbon black/solution-styrene-butadiene rubber (SSBR), [15] ILCNTs/SSBR, [16] IL-CNTs/SSBR/butadiene rubber (BR), [17] silica/styrene-butadiene rubber (SBR), [18] silica/SBR, [19] halloysite nanotubes (HNTs)/SBR, [20] IL-HNTs/ SBR, [21] silica/nitrile rubber NBR, [22] and layered double hydroxide (LDH)/carboxylated nitrile rubber (XNBR). [22] For applications in electrochemical devices, where flexibility, thermal stability and high ionic conductivity are required, polymer electrolytes are frequently based on NBR mixed with an ionic liquid and show greatly enhanced ionic conductivity. [23,24,25] Homogeneous distribution of fillers and increased ionic conductivity are two major reasons for the incorporation of ionic liquids in elastomer composites.…”
Section: Introductionmentioning
confidence: 99%
“…The term lignocellulose is used to describe the three-dimensional polymeric composites that plants create as structural materials. It is composed of variable parts of cellulose, hemicellulose and lignin [12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%